PELATIHAN PENYUSUNAN ARTIKEL ILMIAH HASIL PENELITIAN DAN PARAFRASE GUNA PENGEMBANGAN KARIR GURU SMKN 1 JETIS MOJOKERTO - Annisa Dwi Sulistyaningtyas; Sunyoto Hadi Prayitno; Erlin Ladyawati; Hanim Faizah; Ninik Mutianingsih (STKIP PGRI Sidoarjo, 2021)
Teacher is one the determinants of the high and low quality of education in Indonesia. Not only in teaching, teacher is also required to be able to write a scientific work. This is one of the requirements for career development which will later be used for promotion of functional teacher positions. However, currently there are not many teachers who are capable of writing a scientific paper, thus hampering the process of promotion. Therefore, the implementing team from the Mathematics Education Study Program Universitas PGRI Adi Buana Surabaya, organized training in the preparation of scientific articles and paraphrases for teachers at SMKN 1 Jetis Mojokerto. The training began with the delivery of material on the basic concepts of preparing scientific articles and paraphrases and continued with make a draft of articles. The results of this training are participants understanding of the concept of compiling scientific articles from research results and paraphrase, as well as make a draft of article. Furthermore, the draft of the article is evaluated by the implementing team.